2021
DOI: 10.5194/se-12-1899-2021
|View full text |Cite
|
Sign up to set email alerts
|

Thermal history of the East European Platform margin in Poland based on apatite and zircon low-temperature thermochronology

Abstract: Abstract. The Phanerozoic tectonothermal evolution of the SW slope of the East European Platform (EEP) in Poland is reconstructed by means of thermal maturity, low-temperature thermochronometry, and thermal modelling. We provide a set of new thermochronometric data and integrate stratigraphic and thermal maturity information to constrain the burial and thermal history of sediments. Apatite fission track (AFT) analysis and zircon (U-Th)/He (ZHe) thermochronology have been carried out on samples of sandstones, b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…lower heat flow) in the Late Cre ta ceous zone along the MPT were ob tained from thermochronological ap a tite fis sion-track data (Poprawa and Andriessen, 2006). In the area of EEC east of the TTZ, a re cently ac com plished thermochronological study of Botor et al (2021) sup ple mented by earlier work of Kowalska et al (2019) based on K-Ar dat ing and clay min er als and pro duced a more re li able ther mal his tory of this area. The Me so zoic ther mal his tory of the SW slope of the EEC area was char ac ter ised by grad ual cool ing from peak temper a tures (>120°C) at the tran si tion from the Tri as sic to Ju rassic due to de creas ing heat flow (Botor et al, 2021).…”
Section: Fig 9 Cal Cu Lated Ther Mal Ma Tu Rity and Hy Dro Car Bon Wi...mentioning
confidence: 87%
“…lower heat flow) in the Late Cre ta ceous zone along the MPT were ob tained from thermochronological ap a tite fis sion-track data (Poprawa and Andriessen, 2006). In the area of EEC east of the TTZ, a re cently ac com plished thermochronological study of Botor et al (2021) sup ple mented by earlier work of Kowalska et al (2019) based on K-Ar dat ing and clay min er als and pro duced a more re li able ther mal his tory of this area. The Me so zoic ther mal his tory of the SW slope of the EEC area was char ac ter ised by grad ual cool ing from peak temper a tures (>120°C) at the tran si tion from the Tri as sic to Ju rassic due to de creas ing heat flow (Botor et al, 2021).…”
Section: Fig 9 Cal Cu Lated Ther Mal Ma Tu Rity and Hy Dro Car Bon Wi...mentioning
confidence: 87%
“…A recent apatite and zircon low-temperature thermochronology study postulates an important early Carboniferous uplift in the area of the Baltic Basin, NE of the CDF and Koszalin Fault (Botor et al, 2021). It remains uncertain from the seismic profiles presented whether this uplift was localised along the pre-existing Devonian faults or had a character of long wavelength doming.…”
Section: Discussionmentioning
confidence: 99%
“…A paleothermal investigation of the platform sediments performed recently, using multiple low-temperature thermochronometer methodologies e.g., apatite fission-track (AFT) and zircon (U-Th)/He (ZHe) and a K-Ar analysis of the clay fractions [78][79][80], allows for the identification of a few thermal events, which were related to the area of cratonic foreland of its neighboring orogenic systems. K-Ar dating of the clays from volcanogenic rocks (E Poland and W Belarus) documents [78] a thermal activity event coinciding with the events of the Caledonian orogeny (dated at 417-447 Ma).…”
Section: Paleotemperature Evidencementioning
confidence: 99%
“…was identified more to the south, close to Volyn area. Moreover, thermal modeling [80] showed that significant heating of the Ediacaran and Carboniferous sedimentary successions occurred before the Permian, with maximum paleotemperatures occurring in the earliest and latest periods of the Carboniferous for Baltic-Podlasie and Lublin Basins, respectively [80].…”
Section: Paleotemperature Evidencementioning
confidence: 99%
See 1 more Smart Citation